Absolute Bioavailability of Vemurafenib in Patients With BRAFV600 Mutation–Positive Malignancies. Issue 4 (21st February 2020) - Zhang, Weijiang; Colburn, Dawn; Simmons, Brian; Papai, Zsuzsanna; Bertran, Enric; Schadt, Simone; Husser, Christophe; Forbes, Harper; Roethlisberger, Dieter; Hartung, Thomas
Abstract: Vemurafenib is a BRAF kinase inhibitor indicated for the treatment of patients with BRAF V600 mutation–positive unresectable or metastatic melanoma and Erdheim‐Chester disease. This phase 1, open‐label, single‐arm study was designed to estimate absolute bioavailability of oral vemurafenib at steady state and to characterize the pharmacokinetics of a single intravenous microdose of 14 C‐labeled vemurafenib in patients with BRAF V600 mutation–positive malignancies. Patients received oral vemurafenib 960 mg twice daily on days 1 through 28, with a single intravenous infusion of 14 C‐labeled vemurafenib solution (3 mL, corresponding to a radioactive dose of 18.5 kBq and a vemurafenib dose of 20 µg) given on the morning of day 21, immediately following the morning dose of oral vemurafenib. A total of 6 patients were enrolled. Four patients who received 14 C‐labeled vemurafenib infusion were included in the pharmacokinetic and bioavailability analyses. Geometric mean absolute bioavailability of oral vemurafenib at steady state, calculated as the ratio of dose‐normalized area under the curve during the dosing interval (AUCτ ) following oral vemurafenib dose to dose‐normalized AUC from time 0 extrapolated to infinity (AUC0‐inf ) following vemurafenib intravenous dose, was 57.8%. The majority of radioactivity (geometric mean 41%) was recovered in feces, and a small proportion (geometric mean 1.4%) was recovered in urine. Treatment‐emergent adverse events occurred in 5 of 6 (83%) patients and were all grade 1/2 in severity, except for 1 grade‐4 anaphylactic reaction occurring during infusion of 14 C‐labeled vemurafenib, which was thought to be related to the excipient polysorbate 80 in the intravenous formulation.